2018
DOI: 10.1021/acs.jmedchem.7b01760
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships and Computational Investigations into the Development of Potent and Balanced Dual-Acting Butyrylcholinesterase Inhibitors and Human Cannabinoid Receptor 2 Ligands with Pro-Cognitive in Vivo Profiles

Abstract: The enzyme butyrylcholinesterase (BChE) and the human cannabinoid receptor 2 (hCBR) represent promising targets for pharmacotherapy in the later stages of Alzheimer's disease. We merged pharmacophores for both targets into small benzimidazole-based molecules, investigated SARs, and identified several dual-acting ligands with a balanced affinity/inhibitory activity and an excellent selectivity over both hCBR and hAChE. A homology model for the hCBR was developed based on the hCBR crystal structure and used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 74 publications
(139 reference statements)
2
91
0
Order By: Relevance
“…Results from further studies were in accordance with the role of BuChE in AD brains and showed a positive correlation between selective BuChE inhibition and improved cognitive performance and memory [9,10].…”
Section: Introductionsupporting
confidence: 74%
“…Results from further studies were in accordance with the role of BuChE in AD brains and showed a positive correlation between selective BuChE inhibition and improved cognitive performance and memory [9,10].…”
Section: Introductionsupporting
confidence: 74%
“…A recent experiment with AChE knockout mice supported this hypothesis [ 9 ]. Results from further studies were in accordance with the role of BuChE in AD brains and showed a positive correlation between selective BuChE inhibition and improved cognitive performance and memory [ 10 , 11 ].…”
Section: Introductionsupporting
confidence: 63%
“…Besides that, it has been shown that BChE (over-)expression is associated with senile plaques and the transformation of non-fibrillar to fibrillary Aβ plaques. Hence, inhibition of BChE may be more therapeutically valuable than inhibition of AChE in later stages of AD and researches on selective BChE inhibitors are paid wide attention to in recent years 38 , 39 . In this study, the synthesized compounds to some degree showed inhibitory selectivity over BChE, although their potencies were not strong enough as nanomolar level, which at least gave a clue to search for new skeleton frame responsible for multifunctional PARP-1 and cholinesterase inhibition.…”
Section: Resultsmentioning
confidence: 99%